Comparison of the Accuracy and Clinical Parameters of Patient-Specific and Conventionally Bended Plates for Mandibular Reconstruction - Möllmann, Henriette L.; Apeltrath, Laura; Karnatz, Nadia; Wilkat, Max; Riedel, Erik; Singh, Daman Deep; Rana, Majeed (Frontiers in Oncology, 2021)
Objectives This retrospective study compared two mandibular reconstruction procedures—conventional reconstruction plates (CR) and patient-specific implants (PSI)—and evaluated their accuracy of reconstruction and clinical outcome. Methods Overall, 94 patients had undergone mandibular reconstruction with CR (n = 48) and PSI (n = 46). Six detectable and replicable anatomical reference points, identified via computer tomography, were used for defining the mandibular dimensions. The accuracy of reconstruction was assessed using pre- and postoperative differences. Results In the CR group, the largest difference was at the lateral point of the condyle mandibulae (D2) -1.56 mm (SD = 3.8). In the PSI group, the largest difference between preoperative and postoperative measurement was shown at the processus coronoid (D5) with +1.86 mm (SD = 6.0). Significant differences within the groups in pre- and postoperative measurements were identified at the gonion (D6) [t(56) = -2.217; p = .031 <.05]. In the CR group, the difference was 1.5 (SD = 3.9) and in the PSI group -1.04 (SD = 4.9). CR did not demonstrate a higher risk of plate fractures and post-operative complications compared to PSI. Conclusion For reconstructing mandibular defects, CR and PSI are eligible. In each case, the advantages and disadvantages of these approaches must be assessed. The functional and esthetic outcome of mandibular reconstruction significantly improves with the experience of the surgeon in conducting microvascular grafts and familiarity with computer-assisted surgery. Interoperator variability can be reduced, and training of younger surgeons involved in planning can be reaching better outcomes in the future.